Monetary aggregation theory and nominal GDP targeting. (17th June 2019) - Barnett, William A.; Su, Liting
We investigate bivariate time series properties of Divisia money and nominal GDP to investigate the viability of recent proposals advocating a role for a Divisia monetary aggregate in nominal GDP targeting. There are two particularly relevant proposals: 1) the proposal by Barnett, Chauvet and Leiva-Leon (2015) to use a Divisia monetary aggregate as an indicator in the monthly Nowcasting of nominal GDP, as needed in implementation of any nominal GDP targeting policy; 2) the proposal by Belongia and Ireland (2015) to use a Divisia monetary aggregate as an intermediate target, with nominal GDP being the final target of policy. We run well known diagnostic tests of bivariate time series properties of the Divisia M2 and nominal GDP stochastic processes. Those tests are for properties that are necessary, but not sufficient, for the conclusions of Belongia and Ireland (2014) and Barnett et al. (2015). We find no time series properties that would contradict those implied by either of those two approaches.